INNOVATION IN DEVELOPING LANGUAGE TEACHING MATERIALS BASED ON LOCAL WISDOM OF ACEHNESE FOLKTALES FOR SMPN 1 GEMPANG STUDENTS TO IMPROVE LANGUAGE SKILLS IN RURAL ACEH AREAS - Verawati; Lustyantie, Ninuk; Chaeruman, Uwes Anis (Esteem Journal of English Education Study Programme, 2025)
In order to improve the proficiency of the language in Aceh's rural areas, this study intends to create teaching materials for students at SMPN 1 Gempang based on Acehnese folktales. It is anticipated that the incorporation of local wisdom into the creation of teaching materials will significantly enhance the proficiency of the language, especially in social and cultural contexts that are pertinent to the students' surroundings. The study uses a research and development (R&D) approach by modifying the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results demonstrate that the teaching materials created by incorporating Acehnese folktales improve students' comprehension of the local language and culture and boost their motivation to learn. Additionally, the trial results of the teaching materials show a notable improvement in language skills, particularly in speaking, listening, reading, and writing. This study has significant implications for the growth of locally-based language education in rural areas and provides a contextual and sustainable teaching model.